2017
DOI: 10.1088/2053-1583/aa7452
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoresistance of vertical Co-graphene-NiFe junctions controlled by charge transfer and proximity-induced spin splitting in graphene

Abstract: Graphene is hailed as an ideal material for spintronics due to weak intrinsic spin-orbit interaction that facilitates lateral spin transport and tunability of its electronic properties [1-3], including a possibility to induce magnetism in graphene [4-9]. Another promising application of graphene is related to its use as a spacer separating ferromagnetic metals (FMs) in vertical magnetoresistive devices [10-20], the most prominent class of spintronic devices widely used as magnetic sensors. In particular, few-l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
121
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(138 citation statements)
references
References 50 publications
5
121
0
3
Order By: Relevance
“…This is the largest reported value for wet-transferred CVD graphene, thus demonstrating the importance of preserving the quality of the interfaces. Similarly, in 2016 Asshoff et al [39] reported on the exfoliation and transfer of graphene on membranes with holes with a measured MR of about 1%. While the improvement in measured spin signals demonstrated in these studies points to the importance of preserving high-quality FM/2DM interfaces, the signal quality remained far from what was expected.…”
Section: Working With Exfoliated and Transferred Graphenementioning
confidence: 91%
See 3 more Smart Citations
“…This is the largest reported value for wet-transferred CVD graphene, thus demonstrating the importance of preserving the quality of the interfaces. Similarly, in 2016 Asshoff et al [39] reported on the exfoliation and transfer of graphene on membranes with holes with a measured MR of about 1%. While the improvement in measured spin signals demonstrated in these studies points to the importance of preserving high-quality FM/2DM interfaces, the signal quality remained far from what was expected.…”
Section: Working With Exfoliated and Transferred Graphenementioning
confidence: 91%
“…Another striking issue concerned the out-of-plane electrical conduction in devices encompassing only a graphene layer between the two ferromagnetic electrodes, with still no experimental consensus yet on the role of the graphene spacer. Some of the earlier mentioned studies reported on graphene acting mainly as a metallic spacer [20,21,24,32,39], whilst other studies reported on it acting as a tunnel barrier [14,24,28]. One study [25] even reported that its role varied with temperature.…”
Section: Spin Filtering At the Fm/graphene Interfacementioning
confidence: 99%
See 2 more Smart Citations
“…Theoretical estimates, mostly based on DFT calculations, for related systems give values in the 10 −1 − 10 1 meV range [10,[31][32][33][34][35][36]. Experimental values for these couplings also show a significant variety, although they tend to be smaller than the the theoretical predictions, 0.1 meV [2,3,6,[10][11][12][37][38][39][40]. The reason for this discrepancy is likely to be the uncertainty on the graphene-substrate distance, and the degree of commensurability between graphene and the substrate.…”
mentioning
confidence: 99%